Analisa Perencanaan Strategis Sistem Informasi Data Konversi Mahasiswa Program MBKM dengan Metode Ward and Peppard - Latjuba Sofyana STT (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Universitas PGRI Madiun (UNIPMA) has implemented MBKM since 2020. UNIPMA has received assistance from the MBKM program, one of which is the informatics engineering study program. The focus of the MBKM program is on learning outcomes. In accordance with Permendikbud Number 3 of 2020 concerning National Standards for Higher Education, that in a semester the credits recognized in MBKM activities are equivalent to 20 credits. Furthermore, these 20 credits must be converted to courses in the study program. The purpose of this research is the value conversion process is done manually. The conversion team must work hard to sort out learning outcomes that are in accordance with the courses taken by students outside the study program/college. In the future, there will be more and more students participating in the MBKM program, so that if you convert values ​​manually, it will prolong the conversion process. This study focuses on strategic planning of information systems using the Ward and Peppard method using SWOT, value chain and PEST analysis. This is because this method considers the internal and external business environment of the organization. The results of the research are in the form of a suggestion that the MBKM program conversion data information system is feasible to build and needs to be continued for the system design stage. So that later the information system can support and facilitate the conversion process of learning outcomes to MBKM program for informatics engineering study program.